Surgical management of an open, comminuted, intra-articular crush injury to the first metatarsal head: A unique case study - Nikita Grama, DPM, AACFAS; Amber M. Kavanagh, DPM, AACFAS; Brian J. Burgess, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
First metatarsal comminuted fractures are rare and debilitating injuries. They can lead to a host of complications including infection, deformity, malalignment, transfer pressure, and early onset first metatarsophalangeal joint arthritis. They are not well reported in the literature and rarely involve the first metatarsal head. We present a case report of a 17 year-old patient who sustained an open comminuted fracture of the first metatarsal head after dropping a weight on his foot. This was treated with staged procedures, resulting in open reduction and reconstruction of the metatarsal head with placement of external fixator device. He went on to full bony union with resolution of pain, full return to activity, and salvage of the first metatarsophalangeal joint. This is an uncommon case that can lead to disastrous outcomes. The goal of this paper is to outline the steps for surgical reconstruction of the first metatarsal head in order to achieve a functional first ray while avoiding a first metatarsophalangeal joint arthrodesis in a young, active patient.